3.6 Systems with Three Variables

Slides:



Advertisements
Similar presentations
3.6 Systems with Three Variables
Advertisements

3-2 Solving Systems Algebraically (p. 125) Algebra 2 Prentice Hall, 2007.
3-2: Solving Linear Systems
Solving a System of Equations by ELIMINATION. Elimination Solving systems by Elimination: 1.Line up like terms in standard form x + y = # (you may have.
Solving a System of Equations using Multiplication
5.3 Solving Systems using Elimination
Solving Linear Systems using Linear Combinations (Addition Method) Goal: To solve a system of linear equations using linear combinations.
Solving Systems of Equations
 Solve one of the equations for one of the variables.  Isolate one of the variables in one of the equations.  Choose whichever seems easiest.  Substitute.
Warm Up 12/5 1) Is (-2, 3) a solution? 3x + y = -3 3x + y = -3 2x – 4y = 6 2x – 4y = 6 2) Find the solution by graphing y = -4 + x x + y = 6 3) Solve:
Solving Systems of Equations. Solve systems of equations using addition and subtraction.
SOLVING SYSTEMS ALGEBRAICALLY SECTION 3-2. SOLVING BY SUBSTITUTION 1) 3x + 4y = 12 STEP 1 : SOLVE ONE EQUATION FOR ONE OF THE VARIABLES 2) 2x + y = 10.
3.2 Solving Linear Systems Algebraically p Methods for Solving Algebraically 1.Substitution Method (used mostly when one of the equations has.
5.2: Solving Systems of Equations using Substitution
6-2B Solving by Linear Combinations Warm-up (IN) Learning Objective: to solve systems of equations using linear combinations. Solve the systems using substitution.
Solving Systems of Equations using Elimination. Solving a system of equations by elimination using multiplication. Step 1: Put the equations in Standard.
Solving Systems Using Elimination
3-2 Solving Linear Systems Algebraically Objective: CA 2.0: Students solve system of linear equations in two variables algebraically.
Elimination Method: Solve the linear system. -8x + 3y=12 8x - 9y=12.
Do Now (3x + y) – (2x + y) 4(2x + 3y) – (8x – y)
Lesson 7.4A Solving Linear Systems Using Elimination.
Chapter 3 Examples Section 5 Solving System of Equations Algebraically with 3 variables.
Chapter 7.3.  Objective NCSCOS 4.03  Students will know how to solve a system of equations using addition.
Solving Systems of Linear Equations in Two Variables: When you have two equations, each with x and y, and you figure out one value for x and one value.
3-2: Solving Linear Systems. Solving Linear Systems There are two methods of solving a system of equations algebraically: Elimination Substitution.
Objective The student will be able to: solve systems of equations using elimination with addition and subtraction.
Elimination Method - Systems. Elimination Method  With the elimination method, you create like terms that add to zero.
Solving a System of Equations by ELIMINATION. Elimination Solving systems by Elimination: 1.Line up like terms in standard form x + y = # (you may have.
objective I Can state the first step for solving systems. I Can solve systems of equations by graphing, substitution or elimination.
Warm Up Find the solution to linear system using the substitution method. 1) 2x = 82) x = 3y - 11 x + y = 2 2x – 5y = 33 x + y = 2 2x – 5y = 33.
ELIMINATION AND GRAPHING Systems of Nonlinear Equations.
Solving Systems of Equations
10.3 Solving Linear Systems
Solving Systems of Linear Equations
The student will be able to:
Solving Systems of Equations
3.4 Solving Systems with 3 variables
Solving Systems of Equations
Solve Systems of Equations by Elimination
3-2: Solving Linear Systems
Break even or intersection
Solve Systems of Linear Equations in Three Variables
Warm up + 4x – 3y = 1 + 9y + 4x = -1 Add the following polynomials 2.
Solving a system of equations by elimination using multiplication.
REVIEW: Solving Linear Systems by Elimination
Solve Systems of Equations by Elimination
3.5 Solving systems of equations in 3 variables
Solve Systems of Linear Equations in Three Variables
Bellwork Solve the following equations for y
Notes Solving a System by Elimination
Notes Solving a System by Elimination
SOLVING SYSTEMS USING ELIMINATION
Solving Systems of Equations
3-2: Solving Linear Systems
12 Systems of Linear Equations and Inequalities.
Solving Systems of Equations
Solving Systems of Equations by the Substitution and Addition Methods
Systems with Three Variables
Solving Systems of Equations
Elimination Using Multiplication.
Systems of Linear Equations
Solve the linear system.
Solving Systems of Equations
3-2: Solving Linear Systems
SOLVING SYSTEMS OF EQUATIONS.
3.2 Solving Linear Systems Algebraically
3-2: Solving Linear Systems
The Substitution Method
SOLVING SYSTEMS OF EQUATIONS.
SOLVING SYSTEMS OF EQUATIONS.
Presentation transcript:

3.6 Systems with Three Variables

There are three strategies for solving systems with three equations: Solve by elimination Solve an equivalent system Solving by substitution

Solve by elimination x – 3y +3z = -4 2x + 3y – z = 15 4x – 3y –z = 19 Why pick elimination? Note that the y values in this set are inverses. They will go away once you add the equations together. x – 3y +3z = -4 2x + 3y – z = 15 4x – 3y –z = 19 Step 1: Pair the equation to eliminate y, because the y terms are already additive inverses x – 3y +3z = -4 2x + 3y – z = 15 3x +2z = 11 2x + 3y – z = 15 4x – 3y –z = 19 6x -2z =34

3x +2z = 11 6x – 2z = 34 9x = 45 x=5 3 (5) + 2z = 11 15 + 2z = 11 Step 2: Take the two new equations and use elimination to solve for the remaining two variables (in this case, x and z) Plug in x into either equation to solve for z 3x +2z = 11 6x – 2z = 34 9x = 45 x=5 3 (5) + 2z = 11 15 + 2z = 11 2z = -4 z = -2

x=5, z =-2 x – 3y +3z = -4 5 – 3y + 3(-2)=-4 5 – 3y -6 = -4 -3y = -3 Step 3: Substitute the values for x and z back into one of the original equations (whichever seems easier) and solve for y x=5, z =-2 x – 3y +3z = -4 5 – 3y + 3(-2)=-4 5 – 3y -6 = -4 -3y = -3 y=1 x – 3y +3z = -4 2x + 3y – z = 15 4x – 3y –z = 19 (5, 1, -2) is the solution

3x3 Systems #1 2x + y – z = 5 3x - y + 2z = -1 x - y - z = 0

3x3 Systems #1 2x + y – z = 5 3x - y + 2z = -1 x - y - z = 0

Solving an Equivalent System What is an equivalent system? Very similar to the direct elimination method, but in this case you may need to multiply one or more of the equations by a constant in order for a variable to drop out 2x + y – z = 5 x + 4y + 2z = 16 15x + 6y - 2z = 12 Step 1: Pair the equation to eliminate z, because the z terms are already additive inverses in equations #2 2x + y - z = 5 x + 4y +2z = 16 x + 4y + 2z = 16 15x + 6y - 2z = 12 Note: the Zs are inverses in system #2 but not in #1. Multiply the first equation by 2 to get the Zs so that they will drop out

(2x + y - z = 5)2 x + 4y +2z = 16 x + 4y + 2z = 16 4x + 2y -2 z = 10 Step 2: Manipulate the first equation by multiplying by 2. Now the z variable will drop out of the equations when you combine them. (2x + y - z = 5)2 x + 4y +2z = 16 x + 4y + 2z = 16 15x + 6y - 2z = 12 16x + 10y = 28 4x + 2y -2 z = 10 x + 4y +2z = 16 5x + 6y =26 These equations are all ready set up to allow us to eliminate z. Simply add together to get your two variable equation.

5x + 6y =16 (5x + 6y =16) 5 16x + 10y = 28 (16x + 10y = 28) -3 Step 3: Take the two new equations and use elimination to solve for the remaining two variables (in this case, x and y) Again, we do not have a variable that simply drops out for us. Get a common multiple that you can eliminate. In this case the easiest is to get the Ys to cancel 5x + 6y =16 16x + 10y = 28 (5x + 6y =16) 5 (16x + 10y = 28) -3 25x + 30y = 130 -48x - 30y = -84 -23x = 46 x = -2

5(-2) + 6y =26 5x + 6y =26 -10 + 6y = 26 16x + 10y = 28 6y = 36 Y = 6 Plug x= -2 into either equation to solve for y. 5(-2) + 6y =26 -10 + 6y = 26 6y = 36 Y = 6 5x + 6y =26 16x + 10y = 28

2x + y – z = 5 2 (-2) + (6) – z = 5 -4 +6 –z =5 2 – z = 5 -z = 3 Step 4: Substitute the values for x and y back into one of the original equations (whichever seems easier) and solve for y 2x + y – z = 5 2 (-2) + (6) – z = 5 -4 +6 –z =5 2 – z = 5 -z = 3 z = -3 2x + y – z = 5 x + 4y + 2z = 16 15x + 6y - 2z = 12 (-2, 6, -3) is the solution

3x3 Systems #2 x + 2y + z =10 2x – y + 3z = -5 2x – 3y – 5z = 27 Note: this ALMOST Looks like we could solve The system by elimination. What do we have to do to make one if the variables Inverse of one another? -2(x + 2y + z =10) 2x – y + 3z = -5 2x – 3y – 5z = 27

Now try on your own -2x - 4y -2z =-20 2x – y + 3z = -5

Now try on your own -2x - 4y -2z =-20 2x – y + 3z = -5

Solve by Substitution X – 2y + z = -4 -4x + y -2z = 1 2x + 2y – z = 10 Why pick substitution? Note in each equation a different variable is by itself. X – 2y + z = -4 -4x + y -2z = 1 2x + 2y – z = 10 Step 1: Choose one equation to solve for one of its variables. x - 2y + z = -4 x – 2y = -z -4 x = 2y – z - 4 X = 2y – z - 4

-4x + y -2z = 1 -4(2y – z – 4) + y -2z = 1 -8y + 4z + 16 + y -2z = 1 Step 2: Substitute the expression for x into each of the other two equations. -4x + y -2z = 1 -4(2y – z – 4) + y -2z = 1 -8y + 4z + 16 + y -2z = 1 -7y + 2z + 16 = 1 -7y+ 2z = -15 2x + 2y –z =10 2(2y – z – 4) + 2y –z =10 4y – 2z – 8 + 2y –z =10 6y – 3z – 8 =10 6y -3z = 18

-7y + 2z = -15 6y – 3z = 18 (-7y + 2z = -15)3 (6y – 3z = 18)2 Step 3: Take the remaining equations and solve the system to solve for z and y. We need to eliminate a variable. Let’s get rid of z since on of the terms is already negative -7y + 2z = -15 6y – 3z = 18 (-7y + 2z = -15)3 (6y – 3z = 18)2 -21y + 6z = -45 12y – 6z = 36 -9y = -9 y =1 -7y + 2z = -15 -7(1) + 2z = -15 2z = -8 z = -4 Plug y into one of the equations to solve for z

x – 2y + z = -4 x- 2y + z = -4 -4x + y -2z = 1 x -2(1) + (-4) = -4 Step 4: Substitute the values for y and z into one of the original equations x – 2y + z = -4 -4x + y -2z = 1 2x + 2y – z = 10 x- 2y + z = -4 x -2(1) + (-4) = -4 x – 2 – 4 = -4 x – 6 = -4 x = 2 (2, 1, -4) is the solution to the system of equations.

3x3 Systems #3 x – 3y + z =6 2x – 5y – z = -2 -x + y + 2z = 7

3x3 Systems #3 x – 3y + z = 6 2x – 5y – z = -2 -x + y + 2z = 7

3x3 Systems #4 6a + 12b – 8c = 24 9a + 18b – 12c = 30 Hint: can you factor?

3x3 Systems #4 6a + 12b – 8c = 24 9a + 18b – 12c = 30 The a, b, and c terms of the first two equations are the same. They exist as parallel planes, so there will be no solution to this set of equations!

3x3 Systems #5 4x – 6y + 4z = 12 6x – 9y + 6z = 18 5x – 8y + 10z =20

3x3 Systems #5 4x – 6y + 4z = 12 6x – 9y + 6z = 18 5x – 8y + 10z =20 The first two equations will be planes that lie on top of each other. Equations 1 and 3 (or 2 and 3) are planes that will intersect. How do planes intersect? A Line We are looking for one point where all three planes will intersect. In this case we say that there is no unique solution.